The impact of the North Atlantic Oscillation on electricity markets: A case study on Ireland - John A. Curtis; Muireann Á. Lynch; Laura Zubiate (The Economic and Social Research Institute (ESRI), 2015)
The North Atlantic Oscillation (NAO) is a large-scale circulation pattern driving climate variability in north-western Europe. As the deployment of wind-powered generation expands on electricity networks across Europe the impacts of the NAO on the electricity system will be amplified. This study assesses the impact of NAO, via wind-power generation, on the electricity market considering thermal generation costs, wholesale electricity prices and wind generation subsidies. A Monte Carlo approach is used to model NAO phases and generate hourly wind speed time-series data, electricity demand and fuel input data. A least-cost unit commitment and economic dispatch model is used to simulate an island electricity system, modelled on the all-island Irish electricity system. The impact of NAO obviously depends on the level of wind capacity within an electricity system. Our results indicate that NAO phases can affect thermal generation costs by up to 8%, wholesale electricity prices by as much as exteuro1.5/MWh, and that wind power generators receive on average 12% higher remuneration.
Keywords: 330; North Atlantic Oscillation; NAO; electricity; prices; subsidy